The Influence of Company Characteristics on Corporate Social Responsibility Disclosure In Manufacturing Companies Listed on The Idx - Sukmawati Safitri Dewi; Gatot Prabowo; Marhendra Wicaksono (Ridwan Institute, 2021)
A manufacturing company is one company that has a large enough impact on the problem of pollution, as well as the waste that will be generated from the company's operating activities. This study aims to analyze the effect of company characteristics on disclosure of corporate social responsibility in manufacturing companies listed on the IDX. The characteristics of the company consist of size, profitability, leverage, management ownership, and board size. The sampling technique used in this study uses the purposive sampling method in manufacturing companies listed on the IDX listed in ICMD and listed on the IDX website in 2009-2011. consecutive. Of the 143 manufacturing companies listed on the IDX, only 34 companies met the predetermined criteria for the research sample. The data analysis technique was carried out by using the classical assumption test. Hypothesis testing uses multiple linear regression analysis and statistical analysis in the form of F statistical tests and t statistical tests with the help of SPSS 16.0 for windows. The results showed that simultaneously the variable size, leverage profitability, management ownership, and the size of the board of commissioners had an effect on the Corporate Social Responsibility Disclosure (CSRD). Partially, size, management ownership, and board size have an effect on Corporate Social Responsibility Disclosure (CSRD), while profitability and leverage have no effect on Corporate Social Responsibility Disclosure (CSRD).